Sistem Monitoring Panel Surya Berbasis Android Secara Real-Time - Kurnia Setiawan, Dedy; Widjonarko, Widjonarko; Firdaus, Adhani (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2022)
This Android-Based Solar Panel Current and Voltage Monitoring System is intended to be implemented properly by companies or factories where the monitoring system can be carried out in real time and anywhere using Android. This prototype is made using a 30WP solar panel and uses a buck converter as a voltage reducer that enters from the panel which then the current and voltage will be read by the INA219 sensor which is then processed by Arduino so that it can be displayed by Blynk on Android which is of course connected to each other by the internet. This design is also designed when there is an overvoltage there will be a danger alarm notification via a buzzer that sounds. This test is carried out when in charge and discharge conditions which will later be displayed on the blynk when the battery voltage is low or the battery is full so that the charge and discharge process can be carried out by pressing the on or off button on the blynk so that the load will be in two conditions, namely on and off. The battery is in low condition if the voltage is less than 12.3 volts then there will be a notification tone on the blynk, while the battery is in full condition, namely at a voltage of 13.5 volts it will also display a notification which can be displayed by the blynk.